Pathomorphological changes in the placenta during coronavirus infection and its effect on fetuses and babies (Texas Journal of Medical Science, 2022)
In this paper, we performed a structured search for foreign scientific publications on the morphological assessment of the state of placenta in women with coronavirus infection. The publications available in the PubMed, EMBASE, Medline databases from April to September 2020 were analyzed. The purpose of this analysis was to describe and structure the histopathological changes in the placenta of patients with coronavirus infection during pregnancy